Hot water extract from saccharomyces cerevisiae scavenges dpph and reduces senescence associated β-Galactosidase (Sa-β-Gal) in human dermal fibroblasts - Khaizurin Tajul Arifin; Noor Ikhwan Shansuddin; Norwahidah Abdul Karim; Suzana Makpol (Penerbit Universiti Kebangsaan Malaysia, 2022)
Extracts from Saccharomyces cerevisiae are incorporated in a lot of cosmetic products on the market, but the benefits of the extracts lack scientific reports. We tested the toxicity and anti-senescent activity of an extract from S. cerevisiae on an in vitro model, the human dermal fibroblast (HDF) cell culture. We chronicled the development of the extraction method and the subsequent biochemical assays. We used two extraction methods which were hot water extraction and rapid spin. The optimum duration and growth phase to harvest S. cerevisiae were determined by 2,2-diphenyl-1- picrylhydrazyl (DPPH) assay, which also proved that the extracts exhibited antioxidant activity. Hot water extract showed a higher antioxidant activity, and not toxic to HDF. When subjected to senescence-associated β-galactosidase (SA-β-al) assay, the hot water extract significantly reduced the expression of SA-β-Gal in pre-senescent (passage 20, 30 < population doubling < 40) and senescent (passage 30, population doubling > 50) HDF. In conclusion, S. cerevisiae hot water extract possessed antioxidant activity by scavenging DPPH, and anti-senescent activity by reducing the expression of SA-β-Gal in pre-senescent and senescent HDF.